Investigation of single droplet impact on canopy fabric. (April 2019) - Cheng, Han; Sun, Peng; Tan, Yan; Zhang, Yongbo; Wang, Xing
As raindrops impact on the canopy, the impact force and canopy vibration will be produced. And the impacting will seriously affect the deceleration characteristics of the parachute system. However, it is very difficult to obtain the impact force and vibration characteristics by the existing experimental methods. In order to solve the above problem, a two-way fluid structure interaction numerical method was used to investigate the process of single droplet impacting on canopy fabric. The Volume of Fluid (VOF) model was used in fluid calculation and the fabric was described by a thin porous domain. The finite element method was used to calculate the fabric dynamic response. The exchange of coupling information was achieved by a weak method. Based on the above method, a typical raindrop (2.12 mm) impacting on 66 type polyamide grid silk was studied in this article. The numerical results agreed well with the experimental results, which verified the feasibility and accuracy of the method used in this article. More importantly, the impact force and vibration characteristics were obtained. Finally, the effects of impact velocity, water permeability, and fabric pretension on impacting process were analyzed. The method and conclusions could provide a reference for aeronautical lifesaving, printing, and dyeing.